2021
DOI: 10.1002/jbm.a.37279
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage depletion increases target specificity of bone‐targeted nanoparticles

Abstract: Despite efforts to achieve tissue selectivity, the majority of systemically administered drug delivery systems (DDSs) are cleared by the mononuclear phagocyte system (MPS) before reaching target tissues regardless of disease or injury pathology. Previously, we showed that while tartrate‐resistant acid phosphatase (TRAP) binding peptide (TBP)‐targeted polymeric nanoparticles (TBP‐NP) delivering a bone regenerative Wnt agonist improved NP fracture accumulation and expedited healing compared with controls, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Amphiphilic diblock copolymers of poly(styrene-alt-maleic anhydride)-b-poly(styrene) (PSMA-b-PS) were synthesized via reversible addition−fragmentation chain transfer (RAFT) polymerization, as described previously. 6,46,47,78,79 PSMA-b-PS copolymers were then self-assembled into NPs via solvent exchange with a hydrophobic core (PS) and a hydrophilic shell (PSMA). 6,46,47,78,79 DMAEMA NPs, consisting of a pH-responsive core and cationic corona, were self-assembled from poly(dimethylmethacrylate)-bpoly(dimethylaminoethyl methacrylate-co-butyl methacrylate-co-propylacrylic acid) or p(DMAEMA)-b-p(DMAEMA-co-BMA-PAA) also synthesized via RAFT, as described previously.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Amphiphilic diblock copolymers of poly(styrene-alt-maleic anhydride)-b-poly(styrene) (PSMA-b-PS) were synthesized via reversible addition−fragmentation chain transfer (RAFT) polymerization, as described previously. 6,46,47,78,79 PSMA-b-PS copolymers were then self-assembled into NPs via solvent exchange with a hydrophobic core (PS) and a hydrophilic shell (PSMA). 6,46,47,78,79 DMAEMA NPs, consisting of a pH-responsive core and cationic corona, were self-assembled from poly(dimethylmethacrylate)-bpoly(dimethylaminoethyl methacrylate-co-butyl methacrylate-co-propylacrylic acid) or p(DMAEMA)-b-p(DMAEMA-co-BMA-PAA) also synthesized via RAFT, as described previously.…”
Section: ■ Methodsmentioning
confidence: 99%
“…demonstrated that pre‐treatment with clodronate liposome led to a 3‐ and 1.8‐fold reduction of bone‐targeted NPs in the spleen and liver, respectively, resulting in a significant enhancement in bone accumulation. [ 127 ]…”
Section: Disabling Mps To Minimize Nms Clearancementioning
confidence: 99%
“…Ackun-Farmmer et al demonstrated that pre-treatment with clodronate liposome led to a 3-and 1.8-fold reduction of bonetargeted NPs in the spleen and liver, respectively, resulting in a significant enhancement in bone accumulation. [127] To enhance nanodrug delivery to pulmonary fibrotic tissues, Sun et al developed a clodronate liposomal and fibroblast-derived exosomal hybrid drug nanocarrier, where the clodronate can deplete the KC via passive targeting and the homing properties of homologous exosome favor pulmonary fibrosis-specific accumulation and penetration. [128] The nanocarrier significantly enhanced the delivery of nintedanib, an antifibrotic agent approved for treating pulmonary fibrosis, to pulmonary fibrotic lesions and achieved a remarkable improvement in treating pulmonary fibrosis.…”
Section:  Depletion Of Macrophagesmentioning
confidence: 99%
“…Namely, cellular hitchhiking meaning the use of various cells as the particle carriers [190] or the RES blockade (saturation) induced before the MNPs injection [191,192] are exploited to delay the blood clearing and increase targeting capability. Although the suppression of mononuclear phagocyte function is generally achieved by injecting large doses of various nanoparticles [193,194], it can be blocked by the organism's own intact cells as well. In particular, Nikitin et al elegantly demonstrated that the pre-induced macrophage saturation with antibody-sensitized erythrocytes (socalled, cytoblockade of mononuclear phagocyte system) increased the circulation half-life of nanoparticles by up to 32-fold [181].…”
Section: Mnps For Systemic Circulationmentioning
confidence: 99%